A Community Intervention to Decrease Antibiotics Used for Self-Medication Among Latino Adults - Mainous, Arch G. (American Academy of Family Physicians, 2009)
PURPOSE Recent evidence in Latino communities indicates substantial self-medication with antibiotics obtained without a prescription (WORx). We implemented and evaluated a culturally sensitive educational intervention to decrease antibiotic self-medication. METHODS We conducted a community-based intervention with preintervention and postintervention measures in the intervention community (Charleston, South Carolina) as well as a postintervention measure in a control community (Greenville, South Carolina) 200 miles away. The 9-month culturally sensitive intervention included multiple media sources (pamphlets, radio, newspapers). We evaluated the use of antibiotics WORx in the United States, as well as the likelihood of importing antibiotics, by surveying Latino adults in the intervention (n = 250) and in the control community (n = 250). RESULTS Most adults in the intervention community (69%) and the control community (60%) reported some exposure to messages about the inappropriate use of antibiotics, and 25.9% in the intervention community and 8.6% in the control community reported seeing our patient education pamphlets. A substantial proportion of Latino adults in both the intervention (31%) and control communities (20%) have obtained antibiotics WORx in the United States. In multivariate analyses, exposure to an educational message was not a significant predictor of having acquired antibiotics WORx in the United States in past 12 months. The primary predictor of respondents’ having acquired antibiotics WORx in the United States was whether they had bought antibiotics WORx outside the United States. CONCLUSIONS Novel approaches are needed to decrease the use of antibiotics WORx in Latino communities, as focusing only on education may not be sufficient to change behaviors common in their home countries.